Cover Feature: Ionic‐Liquid‐Assisted Microwave Synthesis of Solid Solutions of Sr1−xBaxSnO3 Perovskite for Photocatalytic Applications (ChemSusChem 17/2017). Issue 17 (4th September 2017) - Alammar, Tarek; Slowing, Igor I.; Anderegg, Jim; Mudring, Anja‐Verena
Abstract : The Inside Back Cover picture shows the different perovskite structures obtained by microwave synthesis in ionic liquids, depending on the Sr/Ba content. More details can be found in the Full Paper by Alammar et al. onpage 3387 in Issue 17, 2017 (DOI:10.1002/cssc.201700615 ).